2019
DOI: 10.12659/msm.914905
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Warrick Score and Polysomnographic Parameters in Patients with Interstitial Lung Disease

Abstract: Background Obstructive sleep apnea (OSA) is often reported in connection with interstitial lung disease. As yet, there is insufficient data on the association of OSA severity parameters with lung involvement. We purposed to assess the frequency of OSA in our study group and to investigate the relationship between radiological involvement and OSA severity parameters. Material/Methods The study included 79 patients with interstitial lung disease who underwent spirometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Subgroup analyses were performed to evaluate sources of heterogeneity in the prevalence estimates between studies. The results revealed the prevalence to be higher as 76% (95% CI: 68-83%; I 2 = 69.2%) in the 13 studies enrolling IPF patients [10,[12][13][14][18][19][20][21][22][23][24][25][26] (Fig 2B), whereas in 4 studies including patients with connective tissue associated-ILD or sarcoidosis [20,21,25,26], the pooled prevalence of OSA was much lower (60%, 95% CI: 49-70%; I 2 = 0%), suggesting that the prevalence differed according to the type of DPLDs. Moreover, the prevalence of comorbid OSA in healthy controls and chronic obstructive pulmonary disease (COPD) were examined in two studies, and were found to be less frequent than in IPF (AHI 1.7 ± 1.0 vs 11.6 ± 7.2 [21]; prevalence 44% vs 62% [27]).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Subgroup analyses were performed to evaluate sources of heterogeneity in the prevalence estimates between studies. The results revealed the prevalence to be higher as 76% (95% CI: 68-83%; I 2 = 69.2%) in the 13 studies enrolling IPF patients [10,[12][13][14][18][19][20][21][22][23][24][25][26] (Fig 2B), whereas in 4 studies including patients with connective tissue associated-ILD or sarcoidosis [20,21,25,26], the pooled prevalence of OSA was much lower (60%, 95% CI: 49-70%; I 2 = 0%), suggesting that the prevalence differed according to the type of DPLDs. Moreover, the prevalence of comorbid OSA in healthy controls and chronic obstructive pulmonary disease (COPD) were examined in two studies, and were found to be less frequent than in IPF (AHI 1.7 ± 1.0 vs 11.6 ± 7.2 [21]; prevalence 44% vs 62% [27]).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 94%
“…Quality assessment for each study is summarized in S1 Table. Prevalence of OSA in DPLDs Overall, the pooled prevalence of OSA among DPLDs was 72% (95% CI: 65-79%; I 2 = 75.4%), ranging from 45 to 90% (Fig 2A). Based on 12 studies including 546 patients, which reported severity of OSA [10,12,13,[18][19][20][21][22][23][24][25][26], moderate-severe OSA was observed in 40% patients (95% CI: 28-52%; I 2 = 90.8%), ranging from 8 to 68%, and the pooled prevalence of mild OSA was equally high as 36% (95% CI: 23-48%; I 2 = 91.5%), ranging from 6 to 67%.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Each square represents the effect estimate of a single publication, while horizontal lines represent a 95% confidential interval. The size of squares is proportional to the weight of each paper in the meta-analysis [ 5 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Exact data are available as Supplementary Table S3 .…”
Section: Figurementioning
confidence: 99%
“…In the present study, 46% had mild, 44% had moderate and 10% had severe disease according to Warrick score. Sarac et al [15] reported a lower Warrick score, and their patients had mild to moderate disease. In Farag et al [16] revealed no association between B-lines scores and different grades of disease severity discovered by HRCT.…”
mentioning
confidence: 94%
“…It starts by alveolitis and reaching up to fibrosis. The score vary between 0 [minimum] to 30 [maximum] and higher score indicates severe disease, with high degree of change on radiological study [15] .…”
mentioning
confidence: 99%